Implementasi BPOMM Dalam Mengevaluasi Level Kematangan Proses Bisnis UMKM - Wahyu Ismail Kurnia; Kurnia, Rosna; Tuankotta, Muhamad Hasyim; Alex Kisanjani (Metode : Jurnal Teknik Industri, 2023)
Improving MSME business performance is highly dependent on the level of business process maturity. The higher the level (level) of maturity (Integrated) of a business’s business processes, the more stable and able to achieve competitive advantage. Vice versa, if the maturity level of business processes is at a low level (ad hoc), it will have implications for the stability and inability of the Company to achieve competitive advantage. For this reason, this study aims to adopt the Business Process Orientation Maturity Model framework in assessing the performance of MSMEs through the business maturity process. This research is based on a case study by making UMKM East Kampoeng and Abon Layur Amiroh Salted Fish located in Balikpapan city as research objects. This study uses the business process orientation maturity model (BPOMM) as a model framework and 4 (four) business process maturity levels as a reference for evaluating business process maturity levels. The process of collecting data through the distribution of questionnaires that have been validated by experts and SMEs. While data analysis consists of calculating the assessment results and comparing aspects of business process maturity. The results of the study show that through the BPOMM model framework, the maturity level of the UMKM business processes in East Kampoeng and Shredded Salted Fish Amiroh is at the second level or "Defined". To reach the highest level or "Integrated" the two MSMEs must consistently and irrationally improve aspects of business process maturity that are considered lacking based on recommendations